Increased fat mass negatively influences femoral neck bone mineral density in men but not women - Charoenngam, Nipith; Apovian, Caroline M.; Pongchaiyakul, Chatlert (Frontiers in Endocrinology, 2023)
Background: Obesity is known to be a protective factor against osteoporosis. However, recent studies have shown that excessive adiposity may be detrimental for bone health. Objective: To determine the association of lean mass (LM) and fat mass (FM) with bone mineral density (BMD) in Thais. Methods: Bone density studies of consecutive patients of Srinagarind Hospital, Khon Kaen, Thailand between 2010 and 2015 were reviewed. LM, FM, lumbar spine (LS) and femoral neck (FN) BMD were measured. Lean mass index (LMI) and fat mass index (FMI) were calculated [LMI=LM (kg)/height (m)2, FMI=FM (kg)/height (m)2] and analyzed to determine the association with LS and FN BMD using multiple regression analysis. This study was approved by the institutional ethical committee (HE42116). Results: A total of 831 participants were included. The mean ± SD age was 50.0 ± 16.3 years. In men, LMI (per 1 kg/m2 increase) was positively correlated with FN BMD (g/cm2, β 0.033) and LS BMD (g/cm2, β 0.031), after adjusting for age, height and FMI. Whereas FMI (per 1 kg/m2 increase) was negatively correlated with FN BMD (g/cm2, β -0.015) but not with LS BMD (g/cm2, β 0.005) after adjusting for age, height and LMI. In women, both LMI and FMI were positively correlated with LS BMD (g/cm2, LMI: β 0.012; FMI: β 0.016) and FN BMD (g/cm2, LMI: β 0.034; FMI: β 0.007) with age, height, LMI and FMI included in the model. Conclusion: Our findings indicate that FM has a sex-specific influence on BMD in Thais.